Excellence in Agri-Marketing through National Agricultural Market (NAM) for Sustainability of Indian Farming Sector - Arcot, Purna Prasad; Rao, Chandrasekhar (Archives of Business Research, 2019)
National Agricultural Market (NAM), the most needed e-platform for the integration of agricultural markets across India is considered as an appropriate solution to overcome the challenges and problems faced by the present stakeholders of the Agri-marketing system. Related issues like states fragmentation into multiple market areas monitored by APMCs, different and numerous levy structures, multiple licenses requirement for trading across different mandis, interventions of high net worth bidders in price-fixing, inadequate infrastructural facilities in reaching mandis and non-usage of e-bidding technology, problems of information dissemination causing asymmetry, lack of transparency in price discovery, high market charges, movement controls between state to state, etc are to be addressed on priority basis in order to benefit the farmers and other stakeholders of agri-marketing industry. The need for the effective unified system across the country combining all agri-marketing platforms both at State and National level is the need of the day and has been well understood by our Prime Minister of India, Sri Narendra Modi and his team. The initiative is taken to have a sustainable environment through National Agricultural Market, which was launched on April 14, 2016. This enables a better price to farmers on their produce & improves the efficiency of the supply chain. Sustainable development is one which meets the needs of the present without compromising the ability of future generations to meet their needs. In this paper, the authors have attempted to understand the National Agricultural Market’s success as a means to sustainability in agri-marketing directly and Indian economy growth indirectly. This paper will be partly based on the theoretical concept &somewhat empirical study that deals with the idea of National Agricultural Markets and its relevance in bringing sustainable development in agri-marketing. The theoretical part consists of a critical review of literature relevant to the concept of agricultural production, marketing and unified market system and concludes in an attempt at a more precise formulation of the idea. The empirical part of the study is based on questionnaires served to randomly select traders and farmers of Karnataka state where unified marketing system ReMS is implemented much earlier to NAM. The empirical part of the study is done to provide background information that makes it possible to discuss sustainable growth possibility in a practical context and should therefore not be seen as a direct attempt to confirm the theory. The research will enable a better understanding of NAM’s effort in achieving excellence in agri-marketing and sustainability of farming.